SKRINING FITOKIMIA DAN AKTIVITAS ANTIBAKTERI EKSTRAK AKAR DADANGKAK (HYDROLEA SPINOSA L) TERHADAP BAKTERI - Oktaviani, Mila (Journal of Pharmacy Tiara Bunda, 2023)
Background: Infectious diseases are still a major problem in the world, especially in developing countries, Indonesia. Objective: To determine the antibacterial activity of dadangkak root extract (Hydrolea spnosa L.) against Sterptococcus mutans bacteria using the disc diffusion and dilution methods to determine the MIC (Minimum Inhibitory Concentration) and KBM (Minimum Kill Concentration) values. Method: Extraction used the maceration method and testing for antibacterial activity used the disc diffusion and dilution methods with concentrations of 20%, 40%, 60%, 80% and 100%. Data analysis uses descriptive qualitative and quantitative. Results: Secondary metabolites produced by dadangakak root extract are: alkaloids, flavonoids, tannins and saponins which have antibacterial activity. The antibacterial activity of Dadangkak root extract (Hydrolea spinosa L.) against Streptococcus mutans bacteria using diffusion testing produced an average inhibition zone of 8.22 mm and using the dilution method to find the MIC was found at a concentration of 40%. Meanwhile, KBM was not found in all concentrations. Conclusion: Dadangkak root extract has secondary metabolites, namely: alkaloids, flavonoids, tannins and saponins. Testing of antibacterial activity using the disc diffusion method showed that there was an inhibitory zone produced, Dadangkak (Hydrolea spinosa L.) root extract had an MIC value at a concentration of 40% against Streptococcus mutans bacteria using the dilution method.